KAJIAN KAPASITAS JALAN PANTAI LOSARI DENGAN METODE ANALISIS BERDASARKAN PKJI 2014 - Selviana Walsen; Penina Istia (Jurusan Teknik Sipil, 2022)
Ambon City is the capital of Maluku province, which every year there is an increase in the number of vehicles. So it is necessary to review the traffic density on each road segment. The function of traffic density identification is to estimate the degree of traffic saturation, and to anticipate future traffic developments. One of the roads that needs to be reviewed is street Losari beach. Street Losari beach is the main access in the movement of vehicles to the traditional shopping center of the Ambon city community, namely Mardika Market.In this study, an analytical method was used based on the Indonesian Road Capacity Guide (PKJI 2014). This method uses primary data in the form of the number of vehicles. For validation of PKJI's calculated speed, speed data is also taken. Then the data is processed to estimate the degree of saturation of the road segment.The results of the study illustrate that there are 2 patterns for peak hours, namely Monday 27 January 2020 and Thursday 30 January 2020 at 08-09 am and 17-18 pm. The number of vehicles from the market direction to Amplaz is higher than the number of vehicles from the Amplaz direction to market. The calculated and actual travel speed ranges from 29-36 km/h. Based on the results of the analysis of the degree of road saturation in current conditions, it can be seen that on Monday, January 27, 2020, it has reached 0.83 and is still below the limit set by PKJI (2014) which is 0.85. however, this figure is already close, so anticipation is needed before it reaches 0.85.Keywords: Capacity; Street; Losari beach